Risk factors associated with incident sexually transmitted infections in HIV‐positive patients in the Australian HIV Observational Database: a prospective cohort study. Issue 8 (28th March 2016) - Mulhall, BP; Wright, ST; De La Mata, N; Allen, D; Brown, K; Dickson, B; Grotowski, M; Jackson, E; Petoumenos, K; Foster, R; Read, T; Russell, D; et al.
Abstract : Objectives: We established a subcohort of HIV‐positive individuals from 10 sexual health clinics within the Australian HIV Observational Database (AHOD). The aim of this study was to assess demographic and other factors that might be associated with an incident sexually transmitted infection (STI). Methods: The cohort follow‐up was from March 2010 to March 2013, and included patients screened at least once for an STI. We used survival methods to determine time to first new and confirmed incident STI infection (chlamydia, gonorrhoea, syphilis or genital warts). Factors evaluated included sex, age, mode of HIV exposure, year of AHOD enrolment, hepatitis B or C coinfection, time‐updated CD4 cell count, time‐updated HIV RNA viral load, and prior STI diagnosis. Results: There were 110 first incident STI diagnoses observed over 1015 person‐years of follow‐up, a crude rate of 10.8 [95% confidence interval (CI) 9.0–13.0] per 100 person‐years. Factors independently associated with increased risk of incident STI included younger age [≥ 50 vs . 30–39 years old, adjusted hazards ratio (aHR) 0.4; 95% CI 0.2–0.8; P < 0.0001]; prior STI infection (aHR 2.5; 95% CI 1.6–3.8; P < 0.001), and heterosexual vs . men who have sex with men (MSM) as the likely route of exposure (aHR 0.2; 95% CI 0.1–0.6; P < 0.001). Conclusions: In this cohort of individualsbeing treated with antiretroviral drugs, those who were MSM, who were 30–39 years old, and who had a prior history of STI, were at highest risk of a further STI diagnosis.